“Digital e-learning platforms in the english language teaching-learning process.” - Castrillón Iñiguez, Carla Mishell (2022)
This work aims to carry out an in-depth analysis of the influence of the use of E-Learning Platforms within the teaching-learning process of the English language. Therefore, it was taken as the line of research: "Education, Communication and graphic design for human and social development" and its subline of research: "Innovation in the learning of English as a Foreign Language." These lines have helped develop this research work, responding to the problem of: How does the use of digital platforms influence the English language teaching in the students of Higher Basic Education of the Paul Dirac Private Educational Unit in the elective year 2021-2022? After which, certain factors have been identified that have allowed an analysis within the educational context, which led to establishing the general objective: To analyze the different e-learning platforms for teaching the English language. This research was carried out through the qualitative approach because the teaching-learning process was analyzed. In addition, it has a quantitative approach because the currently used e-learning platforms in English class were identified. There was an intentional, convenient, non-statistic sample which was developed with 8 teachers of the English language area of the Paul Dirac Educational Unit and the students of Higher Basic Education. Hence, this research was oriented to the descriptive research method because it helps to analyze certain factors for the development of EFL Education through bibliographic sources and interaction on the experience of the 8 teachers in the use of E-Learning Platforms. All this through the application of a survey that allowed to collect information necessary to obtain an approach to a more authentic perspective of the analyzed problem focused on using technological tools, obtaining relevant conclusions for this research, and the educational process of teaching English. After the development of this research, it was determined that the use of E-Learning Platforms is a positive contribution as a method of application in English language teaching. Whose impact is reflected in the improvement of the quality of teaching of language teachers through the exploitation of the tools that the E-Learning Platforms have, with the aim that they can be included in the lesson plans and improve the teaching process for English language.